2021
DOI: 10.1186/s40246-021-00361-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of the pharmacogenomics and genomics literacy framework for pharmacists

Abstract: Background Pharmacists play a unique role in integrating genomic medicine and pharmacogenomics into the clinical practice and to translate pharmacogenomics from bench to bedside. However, the literature suggests that the knowledge gap in pharmacogenomics is a major challenge; therefore, developing pharmacists’ skills and literacy to achieve this anticipated role is highly important. We aim to conceptualize a personalized literacy framework for the adoption of genomic medicine and pharmacogenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Genomics and genetic testing applications have significantly changed the way modern clinical routine works. The wide range of testing applications is believed to improve the whole workflow of drug and disease management, on the grounds that it can enhance disease diagnosis, offer personalised therapeutic schemes, reduce the time and money required for treatment, increase a patient’s life expectancy and ameliorate a person's quality of life during therapy [ 1 ]. Although it is proven that genetic testing has a positive impact on clinical practice, its adoption rate remains low across the different healthcare systems due to social, educational, religious, cultural and legal barriers as many studies have previously shown [ 16 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomics and genetic testing applications have significantly changed the way modern clinical routine works. The wide range of testing applications is believed to improve the whole workflow of drug and disease management, on the grounds that it can enhance disease diagnosis, offer personalised therapeutic schemes, reduce the time and money required for treatment, increase a patient’s life expectancy and ameliorate a person's quality of life during therapy [ 1 ]. Although it is proven that genetic testing has a positive impact on clinical practice, its adoption rate remains low across the different healthcare systems due to social, educational, religious, cultural and legal barriers as many studies have previously shown [ 16 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, genetic research has played an essential role in understanding diseases’ pathophysiology and patients’ input, underscoring the impact of personalized medicine (PM). PM as a clinical approach has a beneficial impact on patients, health care delivery systems and researchers by offering adequate therapeutic approaches to each patient and saving time, effort, and money for disease and drug management [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even if pharmacists' contribution to PGx clinical implementation is vital, they have a minimal involvement in the field. As reported in many studies, a great percentage of pharmacists are not aware of PGx and its applications; some of them do not know how pharmacists can be involved in the field and what are their responsibilities, while others claim to have limited or inadequate training [2,[5][6][7][8][9]. Low participation rate can decelerate the adoption of PM applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of outcome-based education, backward design is a framework for identifying required content or activities of the courses, conferences, webinars, or workshops to help graduates or learners achieve desired outcomes or competencies. In pharmacogenomics, several sets of competencies have been developed ( Rahma et al, 2021 ; Gammal et al, 2022 ). For example, the framework and core competencies by the American Association of Colleges of Pharmacy (AACP) are systematically organized into two major categories: foundational genetics concepts, and clinical pharmacogenomics (CP), which is constructed based on 6 domains of entrust able professional activities (EPAs) involving: 1) patient care provider, 2) interprofessional team member, 3) population health promoter, 4) information master, 5) practice manager, and 6) self-developer ( Kanmaz et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%